Education for citizenship: Implications for Christian education in Spain - Paige, Carol A (International journal of Christianity & education, 2020)
The concept of citizenship has changed and evolved over time. Spain, as part of the European Union, has been included in a paradigm shift from a focus on nationalism to the concept of global citizenship. This has spurred a national controversy over the way in which Spanish students should be educated about citizenship. This article provides a concise history of citizenship education in Spain. An overview of the Education for Citizenship and Human Rights (EfC) curriculum is also incorporated with a description of the controversy surrounding its implementation as a mandatory school subject. It concludes with an explanation of Kingdom citizenship and implications and recommendations for Christian schools.